Encyclopedia Brown and the case of the disgusting sneakers - Sobol, Donald J., 1924-2012. (New York : Bantam, 1991)
America's Sherlock Holmes in sneakers continues his war on crime in ten more cases, the solutions to which are found in the back of the book.
Keywords: Literary recreations